Ennis Franciscan Friary, cloister, capital - O'Donovan, Danielle; O'Donoghue, Aisling (My University, 2008)
Cloister capital, moulding comprises: chamfer, bell, chamfered fillet as necking.
Cloister
Keywords: Architecture, Gothic -- Ireland; Ennis (Ireland)--Buildings, structures, etc.; Architecture, Franciscan; Cloisters (Architecture); Gothic capitals (Architecture); Late Medieval; bell capitals